KOMUNIKASI ELECTRONIC WORD OF MOUTH (E-WOM) PARIWISATA KABUPATEN MAJALENGKA DI MEDIA SOSIAL INSTAGRAM MELALUI #MAJALENGKAHITS - Nurhaipah, Titih (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2019)
The desire updated tourist destinations is a search for self-existence, both in the real social world and in cyberspace through Instagram. After fulfilling their wishes, the desire arises to spread information to others. This diffusion of tourist information is known as word of mouth communication. In addition, Instagram becomes an opportunity or a potential for e-WOM communication that can be maximized as a step in the promotion of tourism. Instagram as a social network that has visual advantages will be more advantageous for tourism e-WOM communication activities through #majalengkahits. The objectives of this study include: exploring the potential of e-WOM on Instagram;the role of followers; and the meaning of the hashtag #majalengkahits. The method used in this research is virtual ethnography. According to the results of the research, the potential of long-term e-WOM communication on Instagram will increase tourists' loyalty. This type of communication rotation will greatly affect the increasing number of tourists in the Majalengka district. In addition, the role of follower #majalengkahist includes providers of information, complementary information and tourist invitations. There are several meanings in the use of #majalengkahits that include republishing, becoming a trend / viral, adding information, showing off, inviting sympathies / love, references, facilitating research, increasing promotion and adding followers.